Achieving the cure of follicular lymphoma: is it time to finalize treatment strategies to reach this goal in a subset of patients? - Passucci, Mauro; Assanto, Giovanni; Pulsoni, Alessandro (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
NO ABSTRACT AVAILABLE